An Analysis of the Influence of Local Elements of Fiqh in Nur al-Din al-Raniri's Al-Sirat al-Mustaqim - Hashim, Jamalluddin; Ali, Abdul Karim; Mohd, Hasanulddin (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
This paper is a study of the influence of local elements of fiqh (jurisprudence) found in the manuscript of Al-Sirat al-Mustaqim (Kitab al-Taharah and al-Salah) by Shaykh Nur al-Din al-Raniri (d. 1068H). Al-Sirat al-Mustaqim is the first book of fiqh written in the Malay language in the Malay archipelago. A western orientalist has made the allegation that the works of Malay scholars are merely translations of famous classical texts on fiqh. Therefore, the objective of this study is to examine the truth of this allegation by means of a text study of Al-Sirat al-Mustaqim. This study was conducted using library research, with a focus on data from the manuscript of Al-Sirat al-Mustaqim. The qualitative data was processed according to specific themes based on historical knowledge and is presented in a descriptive manner. The results show that Shaykh Nur al-Din al-Raniri deals with of a number of local fiqh issues in Al-Sirat al-Mustaqim. This proves his sensitivity as a scholar to the requirements, where Islamic law is concerned, in the Malay community in which he livedHence, the allegations are negated. Keywords: local fiqh issues, al-Sirat al-Mustaqim, Shaykh Nur al-Raniri, classical fiqh texts, translation